Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Solve for \( m \):

[tex]\[ (2m + 3)(4m + 3) = 0 \][/tex]


Sagot :

Sure, let's solve the equation \((2m + 3)(4m + 3) = 0\) step by step.

### Step 1: Identify the factors
We are given the equation in factored form:
[tex]\[ (2m + 3)(4m + 3) = 0 \][/tex]

### Step 2: Set each factor equal to zero
For the product of two factors to be zero, at least one of the factors must be zero. Therefore, we can set each factor to zero and solve for \(m\).

#### Factor 1:
[tex]\[ 2m + 3 = 0 \][/tex]

#### Factor 2:
[tex]\[ 4m + 3 = 0 \][/tex]

### Step 3: Solve each equation

#### Solving \(2m + 3 = 0\):
[tex]\[ 2m + 3 = 0 \][/tex]
Subtract 3 from both sides:
[tex]\[ 2m = -3 \][/tex]
Divide by 2:
[tex]\[ m = -\frac{3}{2} \][/tex]

#### Solving \(4m + 3 = 0\):
[tex]\[ 4m + 3 = 0 \][/tex]
Subtract 3 from both sides:
[tex]\[ 4m = -3 \][/tex]
Divide by 4:
[tex]\[ m = -\frac{3}{4} \][/tex]

### Step 4: Write the final solutions
The solutions to the equation \((2m + 3)(4m + 3) = 0\) are:
[tex]\[ m = -\frac{3}{2} \quad \text{and} \quad m = -\frac{3}{4} \][/tex]